Effect of uric acid-lowering therapy on renal function in patients with chronic kidney disease 1-4:Meta-analysis - Yin Ri-ping; Fan Zhen-liang; Yang Meng-fan; Song Li-qun (Linchuang shenzangbing zazhi)
Objective To evaluate the efficacy of uric acid lowering therapy in delaying the progression of chronic kidney disease（CKD）and the incidence of adverse events.Methods The databases of PubMed, Embase, Web of Science, Cochrane Library, CNKI,WanFang and VIP were searched for screening, evaluating and extracting the relevant data from all eligible cohorts and randomized controlled studies on uric acid-lowering therapy for delayed progression of CKD.Finally random effect model or fixed effect model was utilized for summarizing the extracted data.Results Forty-six studies were eventually included（4,947 participants）.Among 37 studies（3,802 participants）,significant differences existed in serum uric acid changes[WMD-160.79,95%CI（-180.93,-140.65）,P<0.001].Combined analysis of 31 studies（3,794 participants）showed significant differences in the changes of estimated glomerular filtration rate（eGFR）[WMD4.62,95%CI（3.33,5.91）,P<0.001]and changes of serum creatinine（Scr）in 23 studies（2,026 participants）showed significant differences[WMD-30.13,95%CI（-37.56,-22.69）,P<0.001].Although uric acid lowering therapy could lower the incidence of renal adverse events in patients with CKD 1-4,it offered no marked benefits in terms of reducing cardiovascular events and all-cause mortality.Conclusion Uric acid lowering therapy can improve glomerular filtration rate and delay the progression of CKD 1-4.However, this protective effect may be influenced by multiple factors.Whether or not uric acid lowering therapy is necessary in clinical practices require specific analysis.